Inhibitory effects of zinc hyaluronate on synoviocyte growth and matrix metalloproteinase-9 activity - Seiji Saito; Keisei Maekawa; Shigeru Kotake (Dove Medical Press, 2009)
Seiji Saito, Keisei Maekawa, Shigeru KotakeInstitute of Rheumatology, Tokyo Women’s Medical University, Tokyo, JapanAbstract: Sodium hyaluronate (Na-HA) is a therapeutic agent used for treating knee arthritis. However, it has been unsuccessfully used in the treatment of knee effusions. Joint effusion results from synovial activation and growth, leading to an increase in the production of matrix metalloproteinases (MMPs), especially MMP-9. This study aimed to determine whether the newly developed zinc hyaluronate (Zn-HA) is more effective than Na-HA in inhibiting the growth of synoviocytes or production and activity of MMPs in rheumatoid synoviocytes. Our results showed that Zn-HA inhibited synoviocyte growth, MMP-9 protein production, and MMP-9 mRNA expression, whereas Na-HA exerted only a slight inhibitory effect on these parameters. Moreover, Zn-HA induced synoviocyte apoptosis, whereas Na-HA did not. These results suggest that Zn-HA retards synoviocyte growth by inducing apoptosis following a decrease in the production of MMP-9 and mRNA. Therefore, it is suggested that Zn-HA can suppress arthritis more efficiently than Na-HA.Keywords: synoviocyte, apoptosis, sodium hyaluronate, zinc hyaluronate, rheumatoid arthritis, MMP-9